Design, synthesis and biological evaluation of 4-aryl-5-aminoalkyl-thiazole-2-amines derivatives as ROCK II inhibitors. Issue 19 (1st October 2020) - Ma, Shuchao; Wang, Linan; Ouyang, Ben; Fan, Meixia; Qi, Junhui; Yao, Lei
Graphical abstract: A series of 4-aryl-5-aminoalkyl-thiazole-2-amines were designed, synthesized, and their inhibitory activity on ROCK II was screened by enzyme-linked immunosorbent assay (ELISA). Compound 10l showed ROCK II inhibitory activity with IC50 value of 20 nM. Abstract: A series of 4-aryl-5-aminoalkyl-thiazole-2-amines were designed and synthesized, and their inhibitory activity on ROCK II was screened by enzyme-linked immunosorbent assay (ELISA). The results showed that 4-aryl-5-aminomethyl-thiazole-2-amines derivatives had certain ROCK II inhibitory activities. Compound 10l showed ROCK II inhibitory activity with IC50 value of 20 nM.